Effect of Formulated Artocarpus champeden Extract on Parasite Growth and Immune Response of Plasmodium berghei-Infected Mice - Aty Widyawaruyanti, - (Hindawi Publishing Corporation, 2020)
Background. The ethanol extract of Artocarpus champeden stem bark (ACEE) has been proven to exhibit antimalarial activity. Despite the antimalarial effects observed, mechanisms of immune response to explain the antimalarial activity of ACEE remain poorly characterized. Here, we show the production of pro- and anti-inflammatory cytokines T helper 1 (Th1: IFN-γ, TNF-α) and T helper 2 (Th2: IL-10) from Plasmodium berghei-infected mice treated with formulated ACEE in order to better characterize the mechanism behind ACEE’s antimalarial activity. In addition, we have also determined the effect of formulated ACEE on parasite growth and liver function. Methods. Balb/c mice were infected with P. berghei strain ANKA and then administered daily doses of ACEE at a dose of 20, 50, and 100 mg/kg BW, and survival time was recorded. We determined the presence of P. berghei in the blood of the infected mice and inhibition of P. berghei growth. In order to assess the liver function of infected mice, we determined aspartate transaminase (AST) and alanine transaminase (ALT) levels. Determination of cytokines Th1 (IFN-γ, TNF-α) and Th2 (IL-10) levels was conducted using enzyme-linked immunosorbent assay (ELISA). Results. We found that formulated ACEE inhibited parasite growth and showed the highest antimalarial activity at 100 mg/kg BW. AST and ALT levels were found to be in the normal range, and there was no significant difference among control and treatment groups (P>0.05). Infected mice treated with formulated ACEE showed a significant increase in the production of IFN-γ on day 7 and an increased production of TNF-α on day 4 and day 7. No effect on IL-10 production was observed. Decreased parasitemia and longer survival time were observed when compared with untreated infected mice. Conclusion. This study suggests that the administration of ACEE was effective in inhibiting P. berghei growth in infected mice and extending survival time. No effect on liver function was observed based on AST and ALT levels. The antimalarial effects of ACEE could be explained in part by the enhanced production of the proinflammatory cytokines IFN-γ and TNF-α. ACEE treatment may provide novel therapeutic strategies for malaria in future.